2008
DOI: 10.1002/mrc.2279
|View full text |Cite
|
Sign up to set email alerts
|

NMR elucidation of a novel (S)‐pentacyclo‐undecane bis‐(4‐phenyloxazoline) ligand and related derivatives

Abstract: The NMR elucidation of a novel ligand (S)-pentacyclo-undecane bis-(4-phenyloxazoline) and related pentacyclo-undecane (PCU) derivatives is reported. Two-dimensional NMR proved to be a powerful technique in overcoming the difficulties associated with the elucidation of these compounds when only one-dimensional NMR data is utilized. A chiral substituent was introduced to both 'arms' of the PCU skeleton to produce derivatives 1-3. These derivatives display C(1) symmetry with all thecage atoms being nonequivalent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…One would therefore expect a 3 J ‐coupling constant of about 2–3 Hz according to the Karplus relationship 33. However, in all our previous NMR studies5–11, 14, 28, 34 of the PCU skeleton, this fine coupling constant is never observed. The 1 H NMR spectrum of the peptide 2 (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…One would therefore expect a 3 J ‐coupling constant of about 2–3 Hz according to the Karplus relationship 33. However, in all our previous NMR studies5–11, 14, 28, 34 of the PCU skeleton, this fine coupling constant is never observed. The 1 H NMR spectrum of the peptide 2 (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The NOESY spectra of the PCU cage normally show5–10 correlations of H‐4a with H‐2 and H‐6, whereas H‐4s shows correlations with H‐9 and H‐10, also NOESY and COSY spectra of PCU cage normally show correlations of H‐4a (δ = 1.26 ppm) and H‐4s (δ = 1.72 ppm) with H‐3 and H‐5 (δ = 2.30 ppm and/or 2.15 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR and computational study of 'cage' molecules such as pentacycloundecane and trishomocubane based compounds has been a major focus of our group for the past 5 years [25][26][27][28][29][30][31][32][33][34][35][36]. We recently reported the NMR elucidation of pentacycloundecane based tetraamines [37,38] which were screened for their anti-tuberculosis activities [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, the emergence of a range of standard 2D NMR techniques has helped a great deal in overcoming these problems. Our group has successfully used 2D NMR techniques to elucidate numerous PCU derivatives [12][13][14][15][16][17][18][19][20][21]. Odisitse et al [22] recently reported potent anti-inflammatory activity for the PCU diamine 9; this discovery led to the design and synthesis of compounds 3-8 which are currently being investigated as potential inflammatory agents while compounds 1 and 2 are precursors to 3 and 4. triethylamine was refluxed under nitrogen for 36 h to obtain the novel compounds 18 and 19.…”
Section: Introductionmentioning
confidence: 99%